(untitled) (Principles and Practice of Clinical Research, 2021)
Evaluating the impact of Clinical and Translational Science Awards (CTSA) programs on the development of clinical research professionals is crucial. To this end, the value of competency-based metrics to assess the professional growth of CTSA awardees is unknown. A needs assessment was conducted to determine the present use and potential need for a competency-based self-assessment tool (CBST) as well as what professional competencies were valued. A mixed-methods retrospective analysis was conducted using prior data from semi-structured interviews and online surveys. Overall, 29 unique CTSA hubs participated. Interview requests and surveys had a response rate of 21% (21 out of 102 contacted) and 33% (21 out of 63), respectively. Six institutions were doubly represented in both interviews and survey responses. Of interviewees, 33% reported existing use of a competency-based assessment tool, and 62%, inclusive of those already using a tool, indicated a clear need for one. Interviewees highlighted that CBSTs should ideally be customizable, soft skill-focused, and complementary to other forms of assessment. Of the survey respondents, 67% reported already using a CBST. Both interview and survey results found that communication and teamwork were highly valued competencies in clinical research professionals. Among CTSA workforce development administrators, there is notable interest in CBSTs, particularly ones that are customizable and soft skill-focused.